Behavioural mechanisms of sexual isolation involving multiple modalities and their inheritance. (21st December 2018) - Moran, Peter A.; Hunt, John; Mitchell, Christopher; Ritchie, Michael G.; Bailey, Nathan W.
Abstract: Speciation research dissects the genetics and evolution of reproductive barriers between parental species. Hybrids are the "gatekeepers" of gene flow, so it is also important to understand the behavioural mechanisms and genetics of any potential isolation from their parental species. We tested the role of multiple behavioural barriers in reproductive isolation among closely related field crickets and their hybrids ( Teleogryllus oceanicus and Teleogryllus commodus ). These species hybridize in the laboratory, but the behaviour of hybrids is unusual and there is little evidence for gene flow in the wild. We found that heterospecific pairs exhibited reduced rates of courtship behaviour due to discrimination by both sexes, and that this behavioural isolation was symmetrical. However, hybrids were not sexually selected against and exhibited high rates of courtship behaviour even though hybrid females are sterile. Using reciprocal hybrid crosses, we characterized patterns of interspecific divergence and inheritance in key sexual traits that might underlie the mating patterns we found: calling song, courtship song and cuticular hydrocarbons (CHCs). Song traits exhibited both sex linkage and transgressive segregation, whereas CHCs exhibited only the latter. Calculations of the strength of isolation exerted by these sexual traits suggest that close‐range signals are as important as long‐distance signals in contributing to interspecific sexual isolation. The surprisingly weak mating barriers observed between hybrids and parental species highlight the need to examine reproductive isolating mechanisms and their genetic bases across different potential stages of introgressive hybridization.